Contribution of small-scale migrant fishing to the emergence of the fishmeal industry in West Africa: Cases of Mauritania, Senegal and the Gambia - Dème, El hadj Bara; Failler, Pierre; Fall, Assane Dedah; Dème, Moustapha; Diedhiou, Idrissa; Touron-Gardic, Grégoire; Bocoum, Waly; Asiedu, Berchie (Frontiers in Marine Science, 2023)
The objective of this article is to present the contribution of migrant fishers to the supply of fishmeal factories in Senegal, The Gambia and Mauritania. The method consisted first of identifying migrant fishers and then quantifying the volumes of small pelagic fish they catch in the three countries studied. Then, an interview guide was submitted to more than 250 actors (migrant fishers and fishmongers) met in Banjul and Serrekunda in the Gambia, in Nouakchott and Nouadhibou in Mauritania, and in the fishing, centers located on the small Senegalese coast. These individual and collective interviews made it possible to estimate and determine the share of migrant fishers’ catches allocated to the fishmeal industry. Overall, the four groups of migrant fishers (3 Senegalese and 1 Guinean) identified in Mauritania and The Gambia catch on average more than 305,000 tonnes of pelagic fish per year over the period 2015 - 2018. Analysis of the marketing of their catches shows that almost 63% of the 305,000 tonnes, i.e. 192,000 tonnes of pelagic fish, are destined to supply the fishmeal factories of the three countries studied, while only 113,000 tonnes are distributed on the national consumer markets (fresh and artisanal processed). Of the 192,000 tonnes destined for fishmeal factories, two-thirds are sent to Mauritanian factories, with Senegal and The Gambia sharing the remaining third. Thus, important collaborations have been established in recent years between migrant fishers and the fishmeal industries. Indeed, the fishmeal industries improve the operating accounts of migrant fishers by ensuring the sale of their catches at more remunerative prices than on the local market at the micro level. However, when analyzed on a large scale, fishmeal industries exert a real pressure on the nutritional security of West African countries, as pelagic fish are the main source of animal protein in Senegal and The Gambia and have been over exploited in recent years. In addition, they prevent access to artisanal processing of their raw material. All these elements raise the question of the urgency of regulating migrant fishers catches on a regional scale and drastically reducing the share allocated to fishmeal processing in favor of local consumption.